Ultrashort Peptides for the Self‐Assembly of an Antiviral Coating. Issue 6 (29th January 2023) - Hu, Tan; Kaganovich, Michaela; Shpilt, Zohar; Pramanik, Apurba; Agazani, Omer; Pan, Siyi; Tshuva, Edit; Reches, Meital
Abstract: Antiviral compounds are important for generating sterile surfaces. Here, two extremely short peptides, DOPA‐Phe‐NH2 and DOPA‐Phe(4F)‐NH2 that can self‐assemble into spherical nanoparticles with antiviral activity are presented. The peptide assemblies possess excellent antiviral activity against bacteriophage T4 with antiviral minimal inhibitory concentrations of 125 and 62.5 µg mL −1, for DOPA‐Phe‐NH2 and DOPA‐Phe(4F)‐NH2, respectively. When the peptide assemblies are applied on a glass substrate by drop‐casting, they deactivate more than 99.9% of bacteriophage T4 and Canine coronavirus. Importantly, the peptide assemblies have low toxicity toward mammalian cells. Overall, the findings can provide a novel strategy for the design and development of antiviral coatings for a decreased risk of viral infections. Abstract : Two ultrashort dipeptides, DOPA‐Phe‐NH2 and DOPA‐Phe(4F)‐NH2, that self‐assemble into a coating with antiviral activity against bacteriophage T4 and canine coronavirus are designed. The peptide can self‐assemble into nanoparticles in solution and form transparent coatings on a glass substrate with excellent antiviral activity. The findings provide a novel strategy for the design of antiviral coatings to reduce viral infection.